Compositional effects of Si–Mg–Al composite fillers on the interfacial microstructure and high-temperature strength of SiC/SiC brazed joints - Kazuyuki Kohama (Open Ceramics, 2024)
This study proposes the use of Al-added Si–Mg composite fillers for low-temperature joining of SiC while maintaining high-temperature reliability of the joints. SiC was brazed at 1100 °C using the fillers with various compositions, based on Mg-evaporation-induced isothermal solidification of Si. The interfacial microstructure and mechanical properties of the joint were determined for different Al and Mg compositions in the filler. The added Al promoted Mg evaporation during joining, which increased the joint strength by mitigating the brittleness of the Si-based bonding layers. However, metallic Al remained in the bonding layers, which deteriorated the high-temperature joint strength. Higher Mg and Al concentrations in the filler promoted MgAl2O4 formation in the bonding layers that correlated with Al particle refinement. This contributed to an improvement of the joint properties, with the flexural strength at 1200 °C in air exceeding 60 MPa.